Africa at a Crossroads : Future Prospects for Africa after 50 Years of the Organisation of African Unity/African Union - Gumbo, Trynos; Mujuru, Munyaradzi; Simelane, Thokozani; Mutanga, Shingirirai Savious (Book collections on Project MUSE., 2018)
This book is a compilation of selected papers presented during the 8th Africa Institute of South Africa (AISA) Young Graduates and Scholars (AYGS) Conference held at the University of Johannesburg in the year 2014. The three-day conference dubbed, Africa at a Crossroads: Future prospects for Africa after 50 years of the Organisation of African Unity/African Union, voiced young graduates and scholars' views on Africa's future and developmental breakthroughs, as well as its challenges and opportunities. While the annual conference is a capacity building platform for young scientists, it provided a platform for participants to engage in critical dialogue about the African realities and possible, plausible and desirable future for the continent. The book thus provides a critical interrogation of the drivers of change in Africa moving forward, especially as the AU was busy churning out new ideas and mapping out a new vision for the next 50 years. Essentially the book provides insights on national systems of innovation, matrices on poverty, climate change and lastly a reflection on Africa's position in global governance.